Analysis of stomach contents of freshwater stingrays (Elasmobranchii, Potamotrygonidae) from the middle Negro River, Amazonas, Brazil - Shibuya, Akemi; Araújo, Maria Lucia G.; Zuanon, Jansen (Pan-American Journal of Aquatic Sciences, 2009)
Potamotrygonid stingrays are restricted to Neotropical rivers and information on their diet remains scarce. Thus, the prey composition of four freshwater stingray species from the middle Negro River was studied using stomach contents analysis: Potamotrygon motoro (n=40), Potamotrygon orbignyi (n=27), Potamotrygon sp. "cururu" (n=26), and Paratrygon aiereba (n=34). Prey items were identified up to the lowest taxonomic level possible and analyzed with the Index of Relative Importance (%IRI). Teleosteans, crustaceans and insect larvae were consumed by all species in distinct proportions. Potamotrygon motoro fed mainly on palaemonid shrimps (33.8%) and trichodactylid crabs (48.7%). Stomach contents of Potamotrygon orbignyi were composed principally by insects (96.4%), with predominance of gomphid dragonfly larvae. Potamotrygon sp. "cururu" fed on crustaceans (shrimps and crabs: 49.4%) and insect larvae (30.2%). Paratrygon aiereba consumed mainly teleosteans (94.8%), which were composed by a wide variety of species. These results suggest a food partitioning among the four freshwater stingray species, based on the use of different microhabitats and foraging substrates. Different mechanisms of prey detection and capture may also contribute to the differences of prey composition in the stomach contents of these stingray species.
Análise dos conteúdos estomacais de espécies de raias de água doce (Elasmobranchii, Potamotrygonidae) do médio rio Negro, Amazonas, Brasil
Keywords: Anisoptera (dragonflies); Arthropoda; Crustacea; Dasyatidae; Decapoda (crustacea); Elasmobranchii; Gomphidae; Hexapoda; Palaemonidae; Paratrygon Aiereba; Potamotrygon; Potamotrygon Motoro; Potamotrygon Orbignyi; Potamotrygonidae; Trichodactylidae